Assessment of Partial Edentulism Based on Kennedy’s Class I - A Retrospective Study - Baala vignesh.A1 , Revathi Duraisamy2, Ravindra Kumar Jain.M3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Tooth loss is mainly due to the incidence of carious lesions or teeth, periodontal diseases. The aim ofthe study was to evaluate the edentulous status and assessment of Kennedy’s class I in patients visited tosaveetha dental college for the last 3 months. Records of 86000 patients who visited saveetha dental collegebetween June 2019 and March 2020 were reviewed and the data for the present study was segregated fromNov 2020- Jan 20120 with the input data being the presence of kennedy’s class 1 findings. Data collectedwas calculated, tabulated, analysed and compiled using the SPSS statistical software. The prevalence ofpartial edentulism based on kennedy’s class I findings was 14.3%, was more in old aged individuals above60 years with a frequency of 40.5% and between age 51-60 at a frequency of 35.7%. Association was donebetween gender, age and partial edentulism with Kennedy’s class I findings in maxillary and mandibulararch.The association between age and arch partial edentulism showed there was no statistical significancesince p=0.051. The association between gender and arch partial edentulism was statistically significant sincep=0.021. Within the limitations of this study, the prevalence of partial edentulism based on Kennedy’s classI was more in males than females and the maxillary arch was commonly affected than the mandibular arch.